Profile of the learning Facilities and Infrastructure of Sports and Health Physical Education in State Elementary Schools in Bandar Pusaka District, Aceh Tamiang Regency in 2022 - Yoki Afriandy Rangkuti (Universitas Syiah Kuala, 2023)
This research is based on the lack of students' academic scores in physical education and health subjects. Through preliminary observation of complaints of physical education teachers who are influenced by physical education facilities and infrastructure, the existence and condition of physical education facilities are very diverse because the physical education tools are minimal and the conditions are not so good.. In this study, the subject of the study was 12 state elementary schools in Bandar Pusaka District. This research uses a descriptive qualitative type of research. Based on the results of research on the availability of Physical Education learning facilities in elementary schools in Bandar Pusaka District with a good category of 97.85%, 55.83% with a medium category and 80.31% with a damaged category. Meanwhile, physical education learning infrastructure in elementary schools in Bandar Pusaka District is 60.92% with the Very Good category, 60.92% with the good category.Keywords: facilities, infrastructure, physical education,Kec Bandar Pusaka,